A cooperação técnico-científico--transnacional para assistência no setor saúde na Paraíba: as caravanas do coração da rede de cardiologia pediátrica (2011 - 2018) - Tavares, José Wagner de Oliveira (2020)
This research investigates the creation, goals and results of the Paediatric Cardiology Network in Northeast Brazil, run by the State Government of Paraíba and the Non-Governmental Organization Círculo do Coração from Pernambuco, between the years of 2011 and 2018. In order to help make this research deeper and more complete, it brings a collective view of the roots and the historical evolution of the International Cooperation for Development, nationally and internationally, to prove the existence of a cooperative partnership in the state of Paraíba, with the involvement of national and international actors, in the scope of a transnational, triangular, structuring and decentralized cooperation in the heath sector. The research also aims at associating the main theories, concepts, fields, and interests around this technical, scientific and transnational cooperation, through a descriptive and deductive Case Study, representing deep research concerning health support to children and pregnant women in the state of Paraíba, bringing together features of qualitative and quantitative methods and based on International Cooperation, Paradiplomacy, and Epistemic Communities in the health sector, with the following units of analysis: health assistance to children and pregnant women in Paraíba; expertise exchange between national and international professionals and the Paediatric Cardiology Network and Heart Caravans creations. The conclusion is that there was heath support to the state population and international diffusion of the public policy adopted by the State of Paraíba, through scientific publications, nationally and internationally, as a result of this cooperative architecture.